Efektifitas Strategi Pembelajaran dan Motivasi Belajar terhadap Hasil Belajar Matematika - Witri Lestari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2012)
The purpose of this study was to analyze the influence of strategies learning and motivation in learning of mathematics learning outcomes.. The research method used is an experimental method using the technique “factor analysis” with “Two Way Anova. The research is an experiment conducted in SMK BASKARA at class X with 40 students. The results of the analysis studies suggest that: 1) There is influence the learning strategies of mathematics learning outcomes, 2) There is influence motivation in learning of mathematics learning outcomes, 3) there is interaction between learning strategies and motivation in learning of mathematics learning outcomes.